Political grey : areas of ambiguity and contradiction,Positions - Koekemoer, Carmen (Rhodes University, Faculty of Humanities, Department of Fine Art, 2014)
This Master of Fine Arts submission, consisting of a thesis titled 'Political Grey: Areas of Ambiguity and Contradiction' accompanied by an exhibition titled 'Positions', encompasses the concept of leadership while uncovering and expressing its 'grey areas' in a contemporary and undefined moment in South Africa. The concept of leadership has been complicated throughout the thesis in terms of how it is conceptualised in a traditional royal African art context as well as how Leader-Figures have been and are portrayed in both Western and African portrait genres. The notion that the new is built upon the old is continued throughout my thesis and is evident in the accompanying body of work. This notion is expressed on a number of levels: by the re-contextualisation of the print medium; the creative processes described as 'postproduction' which I use in my work; as well as that which is described as a 'post-transitional' moment. The recent political history of the country is considered, with reference made to the anti-apartheid movement and resistance art produced. Printmaking, viewed as an archetypal medium for resistance, is discussed, with reference made to its socio-political role during the 1980s as well as to the extent to which it continues to be used by contemporary artists in a different realm of conflict and change. This is demonstrated by the shift from the medium as a tool for protest to the medium as an instrument of political irony and pointed commentary.
Keywords: Politics in art; Art -- Political aspects -- South Africa; Leadership in art; Portraits, African; Portraits, European; Art and revolutions -- South Africa